Characteristics of elderly diabetes patients: focus on clinical manifestation, pathogenic mechanism, and the role of traditional Chinese medicine - Yang, Xiaofei; Xue, Chongxiang; Chen, Keyu; Gao, Dongyang; Wang, Han; Tang, Cheng (Frontiers in Pharmacology, 2024)
Diabetes mellitus (DM) has become a major public health issue globally, putting an enormous burden on global health systems and people. Among all diseased groups, a considerable part of patients are elderly, while their clinical features, pathogenic processes, and medication regimens are different from patients of other ages. Despite the availability of multiple therapies and techniques, there are still numerous elderly diabetes patients suffering from poor blood glucose control, severe complications, and drug adverse effects, which negatively affect the quality of life in their golden years. Traditional Chinese Medicine (TCM) has been widely used in the treatment of diabetes for several decades, and its relevant clinical practice has confirmed that it has a satisfactory effect on alleviating clinical symptoms and mitigating the progression of complications. Chinese herbal medicine and its active components were used widely with obvious clinical advantages by multiple targets and signaling pathways. However, due to the particular features of elderly diabetes, few studies were conducted to explore TCM intervention on elderly diabetic patients. This study reviews the research on clinical features, pathogenic processes, treatment principles, and TCM treatments, hoping to provide fresh perspectives on the prevention and management strategies for elderly diabetes.